Beyond the orthodox: Heresy in medicine and the social sciences from a cross-cultural perspective - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
An analysis of the concepts of orthodoxy and heresy with due consideration to the social context (historical, religious, cross-cultural dimensions), within which the terms are discussed, leads us to look historically at its European significance embodied in the witch-craze of the 15th-17th centuries. One way to conceptualize heresy is to analyze it in the context of the relationship of the scientists and scientific theories vis-a-vis societal establishment (ie. power bases such as governments, finance bases, public consensus). Today, unorthodoxy lies in attempts to accomplish interdisciplinary work, or in proposing alternative explanatory strategies (as in alternative medicine). A shift in scientific paradigms seems to characterize the revolutionary changes of our era. The foremost challenge in the construction of new paradigms seems to be the ability to effectively integrate the components of emotion or feelings taking into account both those of the researcher as well as those who are being investigated. This will involve a new conceptualization of objectivity. In an era which is distinguished by globalization, such a task necessitates a new level of understanding that integrates gender related analysis as well as the implications of the recognition of cross-cultural interaction and cultural diversity. Copyright (C) 1996 Elsevier Science Ltd.
Keywords: heresy; orthodoxy; paradigm shifts; modern medicine; alternative medicine; gender